Designing effective math interventions : an educator's guide to learner-driven instruction - Hunt, Jessica H.; Ainslie, Jenny (New York, NY : Routledge, 2022)
Design effective, learner-driven math interventions with this accessible and thought-provoking guidebook. Learn how to set up instruction to promote participation and understanding, plan purposeful, targeted tasks, develop student thinking, and create tools to assess student work in a way that measures learning, not just performance. Chapters explore questions that educators frequently struggle with when designing interventions, offering user-friendly research and evidence-based strategies to help overcome common hurdles. This book is essential reading for anyone seeking an adaptive approach to Tier 2 and 3 interventions that positions struggling students as competent learners.
Keywords: Mathematics -- Remedial teaching; Self-culture.; EDUCATION / Special Education / General; EDUCATION / Teaching Methods & Materials / Mathematics